How Optimal is The Visual Display Terminal (VDT) Work Station at The Public Health Faculty, Universitas Airlangga - Fitria Nurus Sakinah (The Indonesian Journal of Occupational Safety and Health, 2020)
Introduction: The academic and student affairs department in the administration room of the Faculty of Public Health of Universitas Airlangga works using a Visual Display Terminal (VDT) with a sitting work position that has the potential to cause eye strain and several muscular disorders. This study aimed to describe the work station of VDT users in the administration room of the Public Health Faculty, Universitas Airlangga. Method: This research was an observational research using cross-sectional descriptive design. The population was the users of the VDT in the administration room of the Public Health Faculty, Universitas Airlangga, as many as 11 people. The sample used was total population. Data were collected using an observation sheet and then was analyzed descriptively. Result: The head position of all workers were optimal (100.0%); the majority of workers' visibility was optimal (54.5%); all table heights were optimal (100.0%); most of the elbow angel and keyboard position was not optimal (63.6%); the majority of mouse positions were optimal (54.5%); chair heights were not optimal (100.0%); most of the backrest and waist angle was optimal (72.7%); most of the workers' knee angles were not optimal (81.8%); most of the legroom were optimal (81.8%); all workstations did not have footing and document holders (100.0%), so they were considered not optimal. Conclusion: Most of the elements is considered as optimal, but some elements are not optimal, including elbow angle, the keyboard position, chair height, knee angle, footing, and document holder.Keywords: work station, sitting work position, visual display terminal